Pelagic ctenophores from the São Sebastião Channel, southeastern Brazil - Oliveira, Otto M.p.; Migotto, Alvaro E. (Zootaxa, 2006)
The ctenophore fauna of Brazilian coast is poorly known. Only one planktonic species, Mnemiopsis leidyi, was previously recorded for the southeastern coast. The present study describes and gives some biological notes of this and four other species (Beroe ovata, Bolinopsis vitrea, Leucothea multicornis, and Ocyropsis crystallina) that occur in the area, two of which (B. vitrea and L. multicornis) are new records for the subtropical southwestern Atlantic.